2021
DOI: 10.3390/w13162214
|View full text |Cite
|
Sign up to set email alerts
|

Do Freshwater Fish Eat Microplastics? A Review with A Focus on Effects on Fish Health and Predictive Traits of MPs Ingestion

Abstract: Microplastics (MPs) have received increasing attention in the last decade and are now considered among the most concerning emerging pollutants in natural environments. Here, the current knowledge on microplastic ingestion by wild freshwater fish is reviewed with a focus on the identification of possible factors leading to the ingestion of MPs and the consequences on fish health. Within the literature, 257 species of freshwater fishes from 32 countries have been documented to ingest MPs. MPs ingestion was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 147 publications
(154 reference statements)
1
24
2
3
Order By: Relevance
“…We observed that 3% of the fish evaluated in our study had ingested microplastics. This low occurrence of plastic particles was much lower than other freshwater fish species reported ( Galafassi et al, 2021 ). Furthermore, the relationship between microplastic ingestion, species, trophic guild, and fishing areas was not evident.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…We observed that 3% of the fish evaluated in our study had ingested microplastics. This low occurrence of plastic particles was much lower than other freshwater fish species reported ( Galafassi et al, 2021 ). Furthermore, the relationship between microplastic ingestion, species, trophic guild, and fishing areas was not evident.…”
Section: Discussioncontrasting
confidence: 63%
“…Specifically, our result may be consistent with the hypothesis that the amount of plastics ingested by omnivorous fish is associated with their wider food web ( Mizraji et al, 2017 ). It has frequently been suggested that fish living in freshwater environments near urbanized regions have a higher risk of microplastic ingestion, and a direct relationship with the level of urbanization has been observed ( Silva-Cavalcanti et al, 2017 ; Souza, Corrêa & Smith, 2020 ; Galafassi et al, 2021 ). However, several studies present evidence that higher environmental concentrations of microplastics do not necessarily translate into higher ingestion by aquatic biota ( McNeish et al, 2018 ; Talley, Venuti & Whelan, 2020 ; Sembiring et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies showed that freshwater fish, along with marine organisms, tend to ingest submerged MPs. According to Galafassi et al [ 17 ], more than 250 species of freshwater fish have been documented to ingest MPs. Plastic microparticle ingestion has been detected in 32 countries, with presence in the digestive tract in more than 50% of the specimens analyzed in one study out of two.…”
Section: Introductionmentioning
confidence: 99%